High Sickness Absence among Part-time Workers in the U.K Food Retail Sector- Unravelling the Truth - Akwensivie, Divine Mawuli; Masereka, Alice Kisembo (Journal of Business and Retail Management Research, 2012)
This paper aims to address two main issues; firstly if it is indeed possible to manage absence due to sickness to the advantage of both the employer and the employee and secondly, to examine if it is indeed possible to use ‘SICK PAY’ to attract and retain part-time workers. This research was undertaken in two stages. A model of motivation theory (Hertzberg 2000) was used to provide a framework upon which to study and answer the research questions. The first stage was conducted by the principal researcher. This involved an informal discussion between the researcher and a group of seven part-time retail assistants of Iceland foods to determine their feelings and opinions about sick pay. This stage of the research provided very important themes and opinions that were used to provide a discussion guide during the second stage of the research. During the second stage of the research a total of twenty part-time retail assistants comprising of Tesco, Sainsbury’s and Marks and Spencer stores were informally interviewed using a combination of different techniques. This was conducted by the two researchers over a period of two months using random sampling technique. During the interviews the researchers were particularly interested in their account of events using a discussion guide prepared in advance of the interviews. This helped the researchers to explore several themes. This research was undertaken from a broadly phemenological and interpretive point of view that lend itself
Keywords: Sickness Absence; Part-time Workers; Food Retail Sector